Perception of Roblox game players toward interest in using Roblox Studio in the Karis Community (a community of female creators and developers in Roblox) - Fatifah Farida; Ichwan Kurniawan; Anas Syaifudin (LPPM Institut Pendidikan Nusantara Global, 2026)
The rapid development of digital technology has encouraged the emergence of interactive platforms that function not only as entertainment media but also as tools for learning and skill development. Roblox is a user-generated content gaming platform that allows users to play and create games through Roblox Studio. This study aims to analyze the perceptions of Roblox game players toward their intention to use Roblox Studio, focusing on members of the Karis Community, a community of female creators and developers on Roblox. This research applies the Technology Acceptance Model (TAM) as the conceptual framework, emphasizing perceived ease of use and perceived usefulness as determinants of behavioral intention to use technology. A quantitative explanatory approach was employed in this study. Data were collected through an online questionnaire distributed to Karis Community members who had experience using Roblox Studio. The research instrument was developed based on TAM constructs and measured using a five-point Likert scale. Data were analyzed using descriptive statistics and multiple linear regression analysis. The results indicate that perceived ease of use and perceived usefulness have a positive and significant effect on behavioral intention to use Roblox Studio. Perceived ease of use shows a stronger influence, indicating that ease in operating the platform encourages continued usage. Perceived usefulness also contributes significantly by demonstrating the benefits of Roblox Studio in supporting creativity and game development activities. These findings confirm the relevance of TAM in explaining technology acceptance within a creative community context.